1988
DOI: 10.1056/nejm198810203191604
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin, Ticarcillin, and Amikacin Compared with Ticarcillin-Clavulanate and Amikacin in the Empirical Treatment of Febrile, Neutropenic Children with Cancer

Abstract: We assessed two antibiotic regimens--vancomycin, ticarcillin, and amikacin, as compared with a vancomycin placebo, ticarcillin-clavulanate, and amikacin--as initial empirical therapy for febrile, neutropenic children with cancer. In a randomized, double-blind clinical trial, the planned 10-day treatment was unsuccessful in 15 percent of the vancomycin, ticarcillin, and amikacin group (n = 53), as compared with 38 percent of the group receiving ticarcillin-clavulanate and amikacin (n = 48) (P = 0.010). Of 10 ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
3
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(44 citation statements)
references
References 30 publications
1
39
3
1
Order By: Relevance
“…It was particularly puzzling that 10 of the 33 were streptococcal species and could not be explained by the use of Hickman catheters. This shift also appears to be occurring in other institutions (8,16,17).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It was particularly puzzling that 10 of the 33 were streptococcal species and could not be explained by the use of Hickman catheters. This shift also appears to be occurring in other institutions (8,16,17).…”
Section: Discussionmentioning
confidence: 70%
“…In 1983, we advocated the use of vancomycin as part of the initial regimen after a trial of ceftazidime monotherapy because we encountered several lethal gram-positive superinfections (12) and we subsequently showed that the addition of van-comycin to ceftazidime abrogated these superinfections (7). Other studies with different antibiotic combinations also supported the need for vancomycin as part of the initial regimen because of the increasing number of gram-positive infections that were being seen as well as for gram-positive superinfections which occurred during therapy (1,4,6,16). However, large studies done by the National Cancer Institute suggested that the addition of vancomycin can be delayed without any resulting increase in morbidity or mortality, even when a gram-positive infection is proven (11,13).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Teicoplanin, an antibiotic administered once daily with activity against strains of enterococci resistant to vancomycin, seems to be less toxic (13,21) and is easier to administer. Both vancomycin (12,22) and teicoplanin (4, 14,16), when used in initial, combined therapy, have proved to be efficacious in the treatment of neutropenic patients with gram-positive bacteremias; however, comparative studies able to establish which glycopeptide antibiotic may be the better choice in febrile, neutropenic patients are lacking.…”
mentioning
confidence: 99%
“…The initial use of vancomycin as part of empiric antibiotic regimens is usually recommended for adequate coverage of infections caused by gram positive organisms that are resistant to ␤-lactam antibiotics. 20 However, Rolston et al 3 reported that adding vancomycin within 48 hours of the onset of fever or infection in patients with gram positive infections was not superior to its introduction or the introduction of other antibiotics (trimethoprim plus sulfamethoxazole, clindamycin, or nafcillin) later in the course of the infection. In that study, the majority of patients who did not respond to the initial regimen responded to other antibacterial therapy.…”
Section: Discussionmentioning
confidence: 99%